Development and Validation of an Authentic Leadership Assesment Rubric for Enhancing Nursing Students’ Leadership: An R&D Study at Universitas Gadjah Mada - EKA PUTRI FAJARI YATI (Journal of Nursing Periodic, 2026)
Introduction: Authentic leadership (AL) has been shown to correlate positively with nurses’ job satisfaction at the Universitas Gadjah Mada Academic Hospital, yet practical assessment tools for AL in undergraduate nursing education remain limited. The objective is to develop, validate, and test the effectiveness of a context-specific authentic leadership assessment rubric for evaluating nursing students’ leadership performance in simulated clinical settings. Methods: A research and development study using the ADDIE model was conducted with 30 expert validators and 120 bachelor nursing students in 2025. The 24‑item rubric was adapted from the Authentic Leadership Questionnaire (ALQ) and organized into four core dimensions. Results: The rubric showed strong content validity (CVI=0.87) and high internal consistency (Cronbach’s alpha=0.845). Exploratory factor analysis confirmed a four-factor structure explaining 71.4% of variance. After a rubric‑guided leadership workshop, students’ leadership scores increased from 3.15±0.58 to 4.12±0.49 on a 5‑point scale (p<0.001, Cohen’s d=1.62). Conclusions: The rubric is valid, reliable, and educationally effective as an authentic assessment tool in Indonesian nursing curricula and has potential to contribute indirectly to improved nurse job satisfaction and retention.